Finite element analyses on a small masonry house prototype retrofitted using frp strips - Habieb, Ahmad Basshofi; Valente, Marco; Milani, Gabriele (Journal of Civil Engineering, 2025)
This study presents a series of finite element analyses on the prototype of masonry house retrofitted using FRP strips. The model of the masonry house refers to the prototype scaled to 1:3 tested in an experimental campaign. The non-linear behavior of masonry is modeled through the Concrete Damage Plasticity (CDP) model, while the FRP and adhesive are modeled as two separated isotropic solid materials with elastic-plastic behavior. A good agreement between experimental and numerical result is obtained, indicating the increase of bearing capacity of the reinforced masonry prototype.